STABILITY ANALYSIS OF A FOURTH-ORDER CANONICAL MEMRISTOR OSCILLATOR - Botta, Vanessa [UNESP]; Moreira, Marilia Davoli [UNESP] (Pushpa Publishing House, 2017)
In this paper, we present a linear analysis of the equilibrium points of a memristor oscillator mathematical model, given by fourth-dimensional system of ODEs depending on five parameters and a piecewise-linear function. Necessary and sufficient conditions for local stability of the equilibrium points are given.
Keywords: memristor oscillator; stability; Routh-Hurwitz criterion